2022
DOI: 10.1002/pssa.202100735
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Surface Roughness and Tensile Strength of Electrodeposited Copper Foils by Composite Additives

Abstract: It is urgent to develop copper foils with low surface roughness, high tensile strength, and good thermal conductivity in electronic equipment communication. Herein, the effect of three single additives (gelatin, polyacrylamide, and thiourea) and two composite additives (gelatin–polyacrylamide and thiourea–polyacrylamide (Tu‐PAM)) on the surface roughness, tensile strength, and thermal conductivity of copper foils fabricated by direct current electrodeposition is investigated. The results show that when Tu‐PAM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Generally, there exists a mechanical performance trade-off between the elongation and tensile strength of ECFs, indicating that an increase in elongation often comes at the expense of sacrificing tensile strength. 11 In the 8 μm ECFs, a strict positive correlation between the RTC of the (100) plane and elongation is not distinctly evident. Moreover, a law similar to that observed in the 6 μm ECFs is also present.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Generally, there exists a mechanical performance trade-off between the elongation and tensile strength of ECFs, indicating that an increase in elongation often comes at the expense of sacrificing tensile strength. 11 In the 8 μm ECFs, a strict positive correlation between the RTC of the (100) plane and elongation is not distinctly evident. Moreover, a law similar to that observed in the 6 μm ECFs is also present.…”
Section: Resultsmentioning
confidence: 89%
“…It can be observed that the RTC values of (100) and (111) are positively correlated with the elongation, while that of (110) is negatively correlated with the elongation. Generally, there exists a mechanical performance trade-off between the elongation and tensile strength of ECFs, indicating that an increase in elongation often comes at the expense of sacrificing tensile strength …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18,22,36 ,] The potential rapidly decreases by about 111.1 mV and then tends to be stable which the addition of HAP in the 1500 s. HAP can uniformly cover a large area of active sites on the cathode surface, which will hinder the discharge of Cu 2+ ions and increase the overpotential of copper reduction, indicating that HAP has a strong inhibitory effect. [ 37–39 ]…”
Section: Resultsmentioning
confidence: 99%
“…[18,22,36,] The potential rapidly decreases by about 111.1 mV and then tends to be stable which the addition of HAP in the 1500 s. HAP can uniformly cover a large area of active sites on the cathode surface, which will hinder the discharge of Cu 2+ ions and increase the overpotential of copper reduction, indicating that HAP has a strong inhibitory effect. [37][38][39] Add different additives (HAP 80 mg L −1 , HP 10 mg L −1 , DPS 8 mg L −1 ) to the VMS. form competitive adsorption on the copper surface, which plays a depolarizing role and accelerates the reduction of Cu 2+ ions.…”
Section: Electrochemical Analysismentioning
confidence: 99%